Nancy Pelosi's Diplomatic Visit Against US-Taiwan Military Agreement Provides China Threat - Gunawan, Yordan; Mareto, Irvan (Indonesian Journal of Law and Society, 2024)
The Chinese government opposes the planned visit of the Chair of the House of Representatives of the United States (US) Nancy Pelosi to Taiwan. Beijing said the trip would endanger the sovereignty and territorial integrity of the Bamboo Curtain state. China is known to claim Taiwan as part of its territory. But Taiwan has repeatedly stated that it is an independent state under the name of the Republic of China. Taiwan has always maintained that Beijing has never ruled it and has no right to speak on its behalf. One of China's efforts to "reunify" Taiwan, as was discussed by President Xi Jinping 2021, said that reunification is a historical mandate and must be fulfilled. China has a military that is superior to Taiwan because apart from taking contingency actions against Taiwan, it is also to face the United States military in the Indo-Pacific. The United States will seek to support a politically, militarily, and economically democratic Taiwan. The US does not have a dismal relationship with Taiwan. But he supports Taipei in dealing with Chinese threats. US President Joe Biden even stated that his state was ready to deploy force if China attacked Taiwan. Keywords: Nancy Pelosi, Diplomatic, One China Policy, Agreement